Biocide activity of Annona coriacea seeds extract on Rhodnius neglectus (Hemiptera: Reduviidae) - Pinheiro Carneiro, Ângela (2013)
The use of synthetic insecticides for insect control may lead to different kind of problems, such as vector resistance to insecticides. To avoid these problems, a new research area to study botanical products as possible disease vectors controls, has become a feasible alternative. The purpose of this research was to evaluate the biocide activity of the ethanol extract of seeds of Annona coriacea on Rhodnius neglectus (Chagas disease vector) nymphs and adults. For this, different concentrations extracts were evaluated: 25, 50, 100 and 200mg/ mL, and water in DMSO (20%) was used as control. The experimental design was completely randomized and we conducted the bioassay with nymphs and adults, with 10 nymphs and 10 adults (five males and five females) per treatment. Extract action was evaluated in both bioassays, in order to identify possible effects of mortality and life cycle interruption of nymphs and adults during a 28-day-period. The results obtained showed that the extract of A. coriacea was able to disrupt the development of nymphs and adults of R. neglectus, with a mortality rate of more than 90%, 36% and 100%, at the highest concentrations, respectively. There was also molting inhibition in nymphs, lower reproductive capacity in females, feeding deterrence and morphological changes in nymphs and adults. We concluded that the extract of A. coriacea has insecticide action on nymphs and adults of R. neglectus.